THE CONTRIBUTION OF TOULMIN'S ARGUMENTATION PATTERNS IN PHYSICS LEARNING IN INDONESIA: LITERATURE REVIEW - Amiruddin, Mohd Zaidi Bin; Sari, Eka Putri Dian Nata; Paramita, Uci Vebia; Suliyanah, Suliyanah; Admoko, Setyo (Jurnal Pendidikan Matematika dan IPA, 2023)
This research is a descriptive research using literature study method which aims to analyze how far is the contribution of Toulmin's Argument Pattern (TAP) in learning physics in Indonesia. The data collection technique used is a review of articles from previous studies related to the application of Toulmin's argument in learning physics. Sources of data used four articles in this research is secondary data. The data obtained were then analyzed using the, organize method, namely organizing the articles to be reviewed, synthesize, which combines the results of organizing articles into an integrated literature,  Identify, which is to identify articles to draw conclusions. Based on the results of the research, it is known that the application of Toulmin's Argumentation in learning Physics in Indonesia has many contributions such as in mastering concepts, problem solving abilities, and especially in improving students' argumentation skills. It is also known that the application of the argumentation-based learning model should be collaborated with problem-based learning models and discussion methods to train students' argument structure preparation. So, for build good argumentation skills, directed teaching is needed by utilizing Toulmin's argumentation pattern.